The Political Ecology of COVID-19 and Compounded Uncertainties in Marginal Environments - Mehta, Lyla; Parthasarathy, D.; Pickard, Justin; Srivastava, Shilpi (Frontiers in Human Dynamics, 2022)
In this paper, we use a political ecology lens to look at how COVID-19 adds to a set of existing uncertainties and challenges faced by vulnerable people in the marginal environments of coastal India. Over the last few decades, local people have been systematically dispossessed from resource commons in the name of industrial, urban and infrastructure development or conservation efforts, leading to livelihood loss. We build on our current research in the TAPESTRY project in coastal Kutch and Mumbai to demonstrate how the pandemic has laid bare structural inequalities and unequal access to public goods and natural resources. The impacts of COVID-19 have intersected with ongoing food, water and climate crises in these marginal environments, threatening already fragile livelihoods, and compounding uncertainties and vulnerabilities. Extreme weather events such as cyclones, droughts, heatwaves and floods in the last couple of decades have also compounded the problems faced in these regions, affecting seasonal migration patterns. We demonstrate how responses from ‘above’ have been inadequate, failing to address problems, or arriving too late. Authoritarian leaders have used the pandemic to ‘other’ and victimise certain groups and polarise society along religious lines. Lockdowns and covid restrictions have been used to surreptitiously complete environmentally destructive infrastructure projects, while avoiding resistance and opposition from affected local communities, who have also been subject to increased surveillance and restrictions on movement. While state responses have often been unpredictable and inadequate, there has been an outburst of local forms of mutual aid, solidarity, and civic action. There are also many examples of resilience at the local level, especially amongst communities that have largely relied on subsistence production. Despite the acute suffering, COVID-19 has also prompted civic groups, activists, and local communities to reflect on the possibilities for reimagining transformative pathways towards just and sustainable futures.